Antioxidant Status And The Effect Of Tocotrienol-Rich-Fraction (Trf) Supplementation On The Antioxidant Enzymes And Development Of Hypertension In Spontaneously Hypertensive Rats (Shr) - Sundaram , Arunkumar (2010)

(untitled)
Adherence to antihypertensive medications in general is not well documented in developing countries, and what is known is far from encouraging. Despite the effectiveness of antihypertensive treatment, medication adherence is often suboptimal in hypertensive Malaysian population. This retro-prospective cohort study aimed to assess the medication adherence, and factors affecting this. A cohort of 380 hypertensive patients was conveniently recruited from the outpatient hypertension clinic at Penang General Hospital, Malaysia. The Morisky self-report scale revealed that 51.3% patients (n=195) had poor adherence to prescribed antihypertensive medication. A Semistructured interview revealed forgetfulness due to a lack of symptoms; poor social support, medication side effects, and the perception that long-term medication may be addictive were principal factors of poor adherence to medication. The structural equation modelling (SEM), which identified the multivariate hypothesized predictors of poor adherence to medication, showed that a lack of self discipline, aversion towards medication, and a negative attitude towards medication in general negatively accounted for 75% of factors affecting medication adherence.